Fundamentals of early childhood education - Morrison, George S. (Upper Saddle River, N.J. Pearson, 2011)
Fundamentals of Early Childhood Education provides a brief, reader-friendly introduction to the field of early childhood education. It presents engaging chapter features on early childhood programs, professionals in practice, diversity strategies, technology issues, and ethical decision-making. Separate chapters on infants and toddlers, preschoolers, kindergartners, and the primary grades explore young children's unique developmental and educational needs. Fundamentals' emphasis on professionalism throughout keeps the focus on meeting the needs of each and every child and providing up-to-date information and strategies to develop competent, informed early childhood professionals.
You and early childhood education : becoming a professional -- Early childhood education today : understanding and responding to current issues -- History and theories : foundations for teaching and learning -- Implementing early childhood programs : applying theories to practice -- Standards and you : teaching children to learn -- Observing and assessing young children : guiding, teaching, and learning -- Infants and toddlers : critical years for learning -- The preschool years : getting ready for school and life -- Kindergarten today : meeting academic and developmental needs -- The early elementary grades : 1-3 : preparation for life -- Educating children with diverse backgrounds and special needs : ensuring each child learns -- Guiding children's behavior : helping children act their best -- Parents, families, and the community : building partnerships for student success -- App. A. Time line of the history of early childhood education.
Keywords: Early childhood education -- United States